Perencanaan Proses Pembelajaran Taḥsīn dan Taḥfīẓ al-Qur’an di Sekolah Dasar Islam Annajah Bekasi - Said Ali Al Musayyieb; Endin Mujahidin; Nesia Andriana; Abas Mansur Tamam; Hasbi Indra (STAI Ali bin Abi Thalib Surabaya, 2023)
This study aims to analyze the planning of the learning process of taḥsīn and taḥfīẓ Al-Qur'an in Annajah Bekasi Islamic Elementary School (SD), as well as the constraints in the learning process. The method used in this research is descriptive qualitative type. Primary data sources were taken from several respondents, namely school principals, curriculum departments, and representatives of taḥsīn and taḥfīẓ teachers randomly. Secondary data sources are from the Al-Qur'an, hadith, journals, books, and others. The background that prompted this research is that Annajah Bekasi Islamic Elementary School (SD) is an elementary level education institution that has serious concern for learning the Qur'an with the Nurul Bayan Method and the Asy-Syafi'i Method. The results of this study are: (1) the planning of the learning process for taḥsīn and taḥfīẓ Al-Qur'an in Annajah Bekasi Islamic Elementary School (SD) is generally neat and orderly according to the learning design model of Dick and Carrey (1985 ), which consists of 10 (ten) systematic learning steps, starting from identifying general learning objectives to designing and carrying out summative evaluations, and (2) some obstacles in the learning process of taḥsīn and taḥfīẓ Al-Qur'an in Annajah Bekasi Islamic Elementary School (SD), among others, that there are students who stammer in reading the Qur'an, lack mastery of the rules of recitation, do not recognize hijā'iyyah letters, and lack motivation in learning. The difference with previous studies is that the focus of the discussion in this research is more broadly related to the analysis of planning the learning process of taḥsīn and taḥfīẓ Al-Qur'an, as well as obstacles in the learning process at Annajah Bekasi Islamic Elementary School (SD) in under the auspices of the Ministry of Education and Culture by using the learning design model Dick and Carrey (1985) as an analytical knife, and the method used refers to the Nurul Bayan Method and the Asy-Syafi'i Method.